Doping sanctions in sport: Knowledge and perception of (legal) consequences of doping. An explorative study in Austria - Cornelia Blank; Magdalena Flatscher-Thöni; Katharina Gatterer; Elisabeth Happ; Wolfgang Schobersberger; Verena Stühlinger (Journal of Risk and Financial Management, 2021)
Anti-doping rule violations (ADRVs) can lead to sports-related and legal sanctions, thus, being knowledgeable is important. Research into this knowledge and how athletes and their support personnel (ASP) perceive the control mechanisms and the appropriateness of (legal) sanctions is still scarce. This explorative study aimed to examine the knowledge and perception of existing (legal) sanctions in Austria, by distributing a questionnaire to Austrian athletes and ASP covering the topics of knowledge related to legal and sports-related consequences associated with a specific ADRV presented in a case study, their trust and satisfaction with specific agencies (based on the European Social Survey (ESS)) and perceived efficiency and effectiveness of the doping control system. Data were analyzed descriptively. All respondents (N = 59) agreed on a ban from sport to be appropriate. Knowledge about legal consequences and the trust in the judiciary and the sport governing bodies was moderate (6.82 out of 10). Perceived appropriate consequences were on average higher than the likely sanctions to be faced. Future prevention should include trust building measures in the institutions and the control system, improvement in terms of access to law and education for the target group and critical reflection on the existence of social norms. Furthermore, the implementation of risk management aspects should be part of future approaches.
Keywords: 330; anti-doping; legal; consequences; ADRV; athlete; athlete support personnel; risk management